Cash flow and corporate performance of companies in hotel and travel industry listed in Colombo stock exchange - Kasthury, S.; Anandasayanan, S. (Sabaragamuwa University of Sri Lanka, 2020)
The life blood of any entities is cash flow where organizations cannot carry out further routine activities or investing activities without sufficient stable cash flow. Because of this, cash flow is of great significance in explaining the finance related symptoms of the entity such as liquidity, profitability and stability. The main intention of this study was to examine how far the cash flow impact on performance of listed Hotel and Travel sector companies in CSE. The research study has been undertaken with data collected from 30 sample companies from 290 Hotel and Travel sector listed companies in CSE using Random Sampling technique and the data is available for 6 years covering from 2013 to 2018. Pooled Ordinary Least Square regression, Fixed Effect and Random Effect and Variance Inflation test were utilized as statistical techniques to explore this study. According to the Hausman test, the Fixed Effect was identified as the best model for examining the impact of cash flow on Return On Assets and Return On Equity. The findings of the study revealed that Operating Cash flow and Investing Cash flow positively and significantly impact on Return on Assets at 95% confidence level. These findings revealed the cost leadership and differentiate strategy used within the hotel and travel sector. On the other hand, financing cash flow has negative and insignificant impact over the Return On Assets which is supported by the agency theory. The value of R squared looks good which is 40% and the Durbin Watson Stat of 2 symbolizes there is no auto correlation. In addition, the multi collinearity problem doesn't exist in the regression model according to the VIF test carried
Keywords: Operating Cash Flow; Investing Cash Flow; Financing Cash Flow; Return on Assets